How to make Facebook your friend: queer self-presentation on a heteronormative social network site. - Russell, Kristin S. (Kansas State University, 2011)
This paper explores queer self-presentation on the social network site, Facebook, emphasizing gendered functionality, gender and queer politics and presentations of gendered identities. It provides a review of early critical cyberculture studies, identity performance and queer theoretical considerations. This study is based on hermeneutic analysis of public profile information and transformative changes of Facebook users as well as in-depth interviews of two queer Facebook users. Results indicate that queer users are always-already gendered, even in the seemingly liberal environment of a social network site, but some, aware of the restrictive structures of Facebook, manipulate presentation to negotiate adequate gender performance. With specific attention to heteronormative structures, this paper challenges former claims of the potential for social progress inherent in social network sites and calls for changes within.
Keywords: Facebook; Gender; Self-presentation; Performance; Queer; Social network site; Cultural Anthropology (0326); Gender Studies (0733); Journalism (0391); Mass Communications (0708); Multimedia (0558); Sociology (0626); Women's Studies (0453)